Проблема української мови в народній просвіті та питання прогресу в українській та російській публіцистиці 1860–1880-х рр. - Єгоров, В. (Український історичний збірник, 2014)
У статті розглядається зміст ідейно-публіцистичної боротьби представників українофільства та реакційно-шовіністичних кіл Російської імперії
навколо проблеми запровадження української мови в початкову освіту українського народу у період 60–80-х рр. XIX ст. В статье рассматривается содержание идейно-публицистической борьбы
представителей украинофильства и реакционно-шовинистических кругов Российской империи по вопросу использования украинского языка в начальном образовании украинского народа в период 60–80-х гг. XIX в. The article considers the publìcistical 1860–80-ies debate of the status, place of
the Ukrainian language in the field of education and training of the Ukrainian people.
There were two opposing points of view on the meaning of progress in the Russian
Empire. in the public domain this discussion reduced to the opposite vision of the
opponents of the supporters of the Ukrainian language. Conservatives proclaimed the
progress as combining all the mental forces under the leadership of the Russian
language, which will give the opportunity to resist the pressure from the outside. On
the other side supporters of the Ukrainian language identified the origin of the
conservatives progress idea — from European ideas of statehood ethnogenesis. They
understood the progress as recognition of state language variety which could spread
the elementary knowledge among the people in their native language.